High Incidence of sepsis caused by MDR bacteria in patients undergoing Percutaneous biliary drainage for the treatment of biliary obstruction. (March 2023) - De Nicola, S.; Cento, V.; Fortunato, M.; Masetti, C.; Colapietro, F.; Pugliese, N.; Ceriani, R.; Bianchi, I.; Pedicini, V.; Lanza, E.; Torzilli, G.; Lleo, A.; et al.
Abstract : Percutaneous biliary drainage (PTBD) is indicated in the management of jaundice and cholangitis caused by biliary obstructions. In an era of increasing prevalence of multidrug resistant (MDR) bacteria the risk of post-PTBD infection is not well established. The aim of our study was to assess the prevalence of post PTBD sepsis driven by MDR bacteria and to identify clinical and epidemiological variables associated with MDR Bacteria. We retrospectively collected data of all consecutive patients who underwent PTBD in our Hospital from January 2015 to January 2020.We recorded the overall incidence of post-procedural sepsis and analyzed various clinical features for their contribution to MDR-sepsis incidence using multivariate linear regression analysis. A total of 99 PTBD were performed in 73 patients during the selected period. The most frequent etiology of biliary obstruction was malignant: Cholangiocarcinoma in 40(54%), Hepatocellular Carcinoma(HCC) in 10(13%) and biliary involvement from other neoplasms in 15 (20%). The median age was 68(range 31-86), male sex was predominant (61%) with 23% of patients having a concomitant chronic liver disease. The majority of patients received cancer treatment prior to PTBD (surgery in 36%, chemotherapy 27%, locoregional treatment in 19%, radiotherapy 19%). Twenty-nine patients (39%) had at baseline a bacterial cholangitis, with only 1 patient infected by a MDR micro-organism prior to PTBD. After PTBD 34/73 (46%) patients developed sepsis, in 9 cases (9/34, 26%) was caused by MDR bacteria(5 ESBL, 2 Amp-C, 2 VRE). At multivariate analysis the only risk factors associated with MDR sepsis were previous local radiotherapy (p=0.01) and baseline AST value (p=0.009). Post PTBD sepsis is frequent in patients undergoing treatment of biliary obstruction. MDR sepsis was found mostly in patients who underwent radiotherapy and had high AST values. Further studies to assess the need for pre PTBD screening for MDR colonization are warranted